FENOMENA JILBAB DALAM PERSPEKTIF SOSIOLOGI - Eko Setiawan (Dialogia: Islamic Studies and Social Journal, 2016)
Abstract: Hijab is an obligation for women Muslim. In sociological perspective, hijab is a social dimension symptom and bring positive value. Moreover, head scarf also has negative value. Now days, hijab is interpreted as individual subjectivity, such as almost people ensure that head scarf is religious orders, belief, fashion and some are many are considered as enforcement.